The relationship between malignancy and Behçet's disease features - DOĞAN, İsmail; ARMAĞAN, Berkan; GÖK, Kevser; KAYACAN ERDOĞAN, Esra; ERTEN, Şükran (Journal of health sciences and medicine : (Turkey), 2022)
Introduction: Behçet’s disease (BD) is an autoimmune, multisystemic vasculitis characterized by chronic inflammation. Autoimmune responses in BD could drive chronic inflammation which is a risk for malignant transformation. Some genetic, environmental, clinical features and immunosuppressive treatments in BD may increase the risk of malignancy. Common genetic factors and similar environmental factors play a role in the pathogenesis of some autoimmune diseases and malignancies. We hypothesized that the frequency of comorbidity and clinical features of BD may differ in BD patients with a family history of malignancy. So, we aimed to compare the demographic and clinical characteristics features of the BD patients with and without a family history of malignancy. Material and Method: The BD patients who admitted the rheumatology outpatient clinic consecutively were included in the study. The demographic and clinical characteristics, comorbidities including malignancy in BD patients and malignancies in their family were questioned. The acute phase reactant elevation of at least two follow-ups was accepted as chronic inflammation. Results: A total of 98 patients (57% male) were included. Mean age was 43.5±12.3 years. The frequency of comorbidity was 60% and malignant/premalignant lesions were seen in 5% of the patients. All lesions were solid organ related and all of them were in women. History of BD and malignancy in patients' families was found 28% and 38%, respectively. The patients with and without malignancy in their family were compared. Female gender and the frequency of erythema nodosum were higher in the patients with malignancy in their family. The other demographic and clinical characteristics, chronic persistent inflammation and medical treatments were statistically. not different Conclusion: Frequency of malignancy in BD patients’ family was evaluated and to the best of our knowledge, there was no literature data on this subject interestingly. The family history of malignancy in BD patients could be associated with clinical characteristics. Further prospective studies were needed to show the clinical effect of malignancy history in families.